Effect of six-week content knowledge workshop on written test performance among physical education students in China - Gao, Yongqi (2023)
The employment problem is particularly prominent among college students majoring in physical education teaching, who are pre service teachers (PE students). In China, students take public institutions' teacher recruitment exams, which comprise 70% written tests and 30% skills. This study investigates the effect of a 6 week content knowledge (CK) workshop on PE students’ written test performance. The objectives are to evaluate the impact of the workshop on the basic theoretical knowledge in sports training d esign (STD) and teaching design (TD), health promotion knowledge in movement energy metabolism (MEM) and movement techniques (KMT), physical movement knowledge in competition venue planning (CVP) and knowledge of movement rules (KMR) on performance in writ ten tests among PE students in China. In addition, this study also aims to evaluate the effect of the workshop on comprehensive CK scores in written test performance among PE students in China. The Randomised Controlled Trial was adopted. Volunteers fro m the Ning Xia Normal University of China participated in this study. Fifty four (54) participants were randomly selected to participate, all of whom were college students majoring in PE teaching in the fourth year. The Chinese standard examination test me asured their performance in written tests. The test content included CK related to STD, TD, MEM, KMT, CVP, and KMR. The participants we re divided into two groups: an experimental and a control group. Baseline information includes gender age home location father and mother education. There were no significant differences on demographic characteristics between intervention and control groups at baseline, which indicates the two groups were comparable.The experimental group underwent a workshop intervention, while the control group followed standard classes planned by the university. Both groups were followed up for a six week intervention program, including three tests: a pre test at week 0, post test one at week 3, and post test two at week 6. Generalized e stimating equations and a two way repeated measures analysis of variance (ANOVA) were used to analyse the data. The results of the GEE showed that the workshop significantly improved students' TD (χ2 = 17.377, P < 0.001), KMT (χ2 = 10.713, P = 0.001), and CVP (χ2 = 13.091, P<0.001) written test performance. However, insignificant written test performance results were reported for STD (χ2 = 0.026, P = 0.872), MEM (χ2 = 1.945, P = 0.163), and KMR (χ2=3.226, P=0.072). Simultaneously, the two way repeated ANOVA results showed that the workshop significantly improved the students' score of comprehensive content knowledge (F = 19.651, P < 0.001, η2 = 0.274). In addition, results also indicated a significant improvement in the written test as early as at 3 weeks of intervention for TD. In conclusion, the workshop improved students' CK, evidenced in their written test performance, especially in TD, KMT, and CVP. The finding expanded the theory by Ward (2009), which investigated the effect of workshops on the teache r (to ascertain whether CK could be taught better to students after undergoing a workshop). The present study found that students’ CK can improve through workshops conducted directly with students to save time and cost while being effective. Future studies should embed the workshop method in year one to three PE classes as this period represents the early stage of learning CK in PE. By graduation, the students' CK is better as they score well on written tests determining their success in applying for a futu re PE teacher job in China.